Cooperation between Local Governments and Private Parties through Corporate Social Responsibility (Csr) Programs (Study on the Government of North Halmahera Regency with PT. Nusa Halmahera Minerals through Program (CSR) - Aisam Aisam; Santi Bintara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The results showed that cooperation between the North Halmahera government and the private sector (PT. NHM) through the corporate social responsibility program has not run smoothly and has no impact on the lives of the people of Kotruk. This can be caused by several factors, namely the relationship between the government and the company (PT. NHM) with poor community, difficulty communication and openness between companies or organizations that manage it. Csr program is an obstacle to cooperation, the plan is unsustainable and the impact of the plan does not improve the quality of life of the people of Telok Ferringhi. In addition, the power of provincial governments to control CSR activities, such as the Minerba Law on mining permits, appears to undermine regional autonomy and the freedom of local governments to control their domestic operations. This is limited by the Minerba Law which regulates the authority and permits of companies authorized by the provincial government, and limits on the authority of local governments in North Halmahera to support PT. HNM promotes the development and welfare of the community in telok ferringhi area through collaboration..